Mini Scale Strain Sensor Based on Michelson Interferometer for Structural Health Monitoring - Amran, Alwani Athilah; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2025)
Structural health monitoring (SHM) is critical for ensuring the safety and longevity of infrastructure. Traditional strain sensing techniques often lack the sensitivity and resolution required to detect small-scale deformations, leading to delayed maintenance and increased risks. This study addresses these limitations by utilising a Michelson interferometer laser system to enhance strain sensing in laboratory-scale SHM. The objectives of this research include designing a Michelson interferometer setup integrated with laser and optical components, generating interference fringes, and improving strain sensing sensitivity and resolution. The experimental setup involves a He-Ne laser, a beam splitter, high-precision mirrors, and a photodetector to monitor fringeshifts caused by applied strain. Controlled bending tests were performed on polycarbonate samples. Results indicate a linear relationship between the bending angle and the optical path change, which was measured through fringe shifts, demonstrating the system’s high sensitivity and accuracy. For example, at a bending angle of 5°, the optical path change was 0.0436 mm; at 10°, it was 0.0872 mm; and at 15°, it was 0.1308 mm. Sensitivity, indicated by the gradient of the graph of optical path change against bending angle, is high because even small changes in bending angle ledto measurable changes in optical path length. Accuracy, reflected in the linear fitting coefficient of the same graph, is also high, as demonstrated by the linear relationship between the bending angleand the optical path change. This study contributes to advancing SHM methodologies by providing a robust, precise, and scalable approach for real-time structural monitoring.